The Current Role of Graphene-Based Nanomaterials in the Sample Preparation Arena - Maciel, Edvaldo Vasconcelos Soares; Mejía-Carmona, Karen; Jordan-Sinisterra, Marcela; da Silva, Luis Felipe; Vargas Medina, Deyber Arley; Lanças, Fernando Mauro (Frontiers in Chemistry, 2020)
Since its discovery in 2004 by Novoselov et al., graphene has attracted increasing attention in the scientific community due to its excellent physical and chemical properties, such as thermal/mechanical resistance, electronic stability, high Young's modulus, and fast mobility of charged atoms. In addition, other remarkable characteristics support its use in analytical chemistry, especially as sorbent. For these reasons, graphene-based materials (GBMs) have been used as a promising material in sample preparation. Graphene and graphene oxide, owing to their excellent physical and chemical properties as a large surface area, good mechanical strength, thermal stability, and delocalized π-electrons, are ideal sorbents, especially for molecules containing aromatic rings. They have been used in several sample preparation techniques such as solid-phase extraction (SPE), stir bar sorptive extraction (SBSE), magnetic solid-phase extraction (MSPE), as well as in miniaturized modes as solid-phase microextraction (SPME) in their different configurations. However, the reduced size and weight of graphene sheets can limit their use since they commonly aggregate to each other, causing clogging in high-pressure extractive devices. One way to overcome it and other drawbacks consists of covalently attaching the graphene sheets to support materials (e.g., silica, polymers, and magnetically modified supports). Also, graphene-based materials can be further chemically modified to favor some interactions with specific analytes, resulting in more efficient hybrid sorbents with higher selectivity for specific chemical classes. As a result of this wide variety of graphene-based sorbents, several studies have shown the current potential of applying GBMs in different fields such as food, biological, pharmaceutical, and environmental applications. Within such a context, this review will focus on the last five years of achievements in graphene-based materials for sample preparation techniques highlighting their synthesis, chemical structure, and potential application for the extraction of target analytes in different complex matrices.